SELECTION - AN IMPORTANT COMPONENT OF INCREASING THE ECONOMIC POTENTIAL OF BEEKEEPING (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The revival of beekeeping should be aimed at fully meeting the needs of the market with competitive products of the industry. It has to be done based on expanded reproduction of the number of bee families, increasing their genetic potential.  Also, must be an improvement of the existing and creation of new breeds of bee, which are well-adapted to natural conditions, the introduction of the intensive technologies of retention, improvement of partnerships between the farms-producers with raw materials and processing enterprises.The purpose of this article is to analyze and summarize the prospects of breeding work aimed at increasing the economic potential of beekeeping in the context of the economic efficiency of beekeeping. This article also defines the economic principles used to ensure the efficiency of pedigree selection as one of the main directions for improving the productivity of bee families.The article analyzes the situation in the field of breeding activities in Ukraine and considers the role of breeding in increasing the productivity of beekeeping farms. It also reveals the achievements, problems, and tasks of breeding at the current level of agricultural production development. It is proved that breeding is the cheapest, the most effective and environmentally-friendly factor in the growth of livestock production. This article identifies priorities of the strategies and action plans for genetic resources for food production and agriculture.The strategic direction of the development of breeding work in beekeeping is to increase the productivity of bee families and resistance to pests. Achieving beekeeping efficiency, which is expressed in the ratio of useful results of its operation to the resources spent, it is possible to implement methods and techniques based on the scientific organization of labor, the progressive experience of developed countries, and the achievements of agrarian and economic sciences in this field.Beekeeping must be developed on an industrial basis. The above factors affect the productivity of the economy and the reduction of costs of material and labor resources. The implementation of directions and measures to stimulate the development of breeding activities in the context of the economic efficiency of beekeeping will help to increase the productivity of bee families, reduce material and monetary costs per one bee family.
Keywords: breed, genetic resources, breeding, breeding activity, breeding work, economic efficiency, performance evaluation